Plasma p-cresol lowering effect of sevelamer in peritoneal dialysis patients: evidence from a Cross-Sectional Observational Study. - Bruna Guida; Mauro Cataldi; Eleonora Riccio; Lucia Grumetto; Andrea Pota; Silvio Borrelli; Andrea Memoli; Francesco Barbato; Gennaro Argentino; Giuliana Salerno; Bruno Memoli (PLoS ONE, 2013)
p-Cresol is a by-product of the metabolism of aromatic aminoacid operated by resident intestinal bacteria. In patients with chronic kidney disease, the accumulation of p-cresol and of its metabolite p-cresyl-sulphate causes endothelial dysfunction and ultimately increases the cardiovascular risk of these patients. Therapeutic strategies to reduce plasma p-cresol levels are highly demanded but not available yet. Because it has been reported that the phosphate binder sevelamer sequesters p-cresol in vitro we hypothesized that it could do so also in peritoneal dialysis patients. To explore this hypothesis we measured total cresol plasma concentrations in 57 patients with end-stage renal disease on peritoneal dialysis, 29 receiving sevelamer for the treatment of hyperphosphatemia and 28 patients not assuming this drug. Among the patients not assuming sevelamer, 16 were treated with lanthanum whereas the remaining 12 received no drug because they were not hyperphosphatemic. Patients receiving sevelamer had plasma p-cresol and serum high sensitivity C-reactive protein concentrations significantly lower than those receiving lanthanum or no drug. Conversely, no difference was observed among the different groups either in residual glomerular filtration rate, total weekly dialysis dose, total clearance, urine volume, protein catabolic rate, serum albumin or serum phosphate levels. Multiple linear regression analysis showed that none of these variables predicted plasma p-cresol concentrations that, instead, negatively correlated with the use of sevelamer. These results suggest that sevelamer could be an effective strategy to lower p-cresol circulating levels in peritoneal dialysis patients in which it could also favorably affect cardiovascular risk because of its anti-inflammatory effect.